Alkynylated diazadioxaacenes: syntheses and properties - Schaffroth, Manuel; Lindner, Benjamin; Vasilenko, Vladislav; Rominger, Frank; Bunz, Uwe H. F. (The journal of organic chemistry, 2013)
We report the successful synthesis of a series of ethynylated dioxadiazaacenes and investigate their properties. We developed a modular Cu-based catalytic procedure to build up [1,4]dioxino[2,3-b]pyrazine motifs starting from only a few building blocks. TIPS-acetylene-substituted benzene-1,2-diol and naphthalene-2,3-diol were reacted with 2,3-dichloropyrazine, 2,3-dichloroquinoxaline, and 2,3-dichlorobenzoquinoxaline to give a set of six novel and well-soluble dioxadiazaacenes. Different reaction conditions for the coupling were tested. Copper catalysis is most effective and gave the best yield of dioxadiazaacenes. The resulting azaoxaacenes were characterized in terms of optical and electronic properties and crystal packing.